Peran Manajemen Strategik dalam Meningkatkan Kinerja Organisasi: Literature Review - Muhammad Ikhsan; Gabriel Bato Malewa Pirade (International Forum of Researchers and Lecturers, 2026)
In the era of globalization and intensifying market competition, strategic management has become a crucial instrument for organizations to maintain a competitive advantage. This study aims to comprehensively examine the role of strategic management in improving organizational performance based on previous research findings. The method used is a literature review with a qualitative-descriptive approach through the collection, evaluation, and synthesis of scientific articles from reputable national and international journals published between 2021 and 2026. The research findings indicate that the stages of strategic management, including strategy formulation, implementation, and evaluation, contribute significantly to improving organizational performance in both financial and non-financial aspects. Determinant factors such as strategic leadership, resource mobilization, and organizational culture alignment are proven to strengthen organizational effectiveness in facing environmental uncertainty. Furthermore, strategic management plays a vital role in building organizational resilience to adapt to dynamic external changes. The implications of this study emphasize the importance for managers and organizational leaders to implement strategic management practices consistently and integratedly to ensure long-term survival and success. The results of this literature synthesis provide a theoretical framework for practitioners in optimizing organizational strategic capabilities amidst complex global challenges.